Supplementation of a tropical low-quality forage with Calliandra calothyrsus improves sheep health and performance, and reduces methane emission - Mwangi, Paul M.; Eckard, Richard; Gluecks, Ilona; Merbold, Lutz; Mulat, Daniel Girma; Gakige, Jesse; Marquardt, Svenja; Pinares-Patino, Cesar S. (Frontiers in Animal Science, 2024)
Ruminant production systems in the arid and semi-arid regions of Sub-Saharan Africa confront severe challenges due to recurring droughts and the intensifying effects of climate change (CC). These systems face stress factors, including poor animal nutrition and gastrointestinal (GIT) parasite burdens which contribute to low animal productivity and a high environmental footprint. These challenges should be addressed by promoting better animal health, enhanced productivity, and reduced environmental impact, to safeguard the livelihoods of rural populations. This 50-day study evaluated the effects of improved feeding and nutritional management in sheep, focusing on GIT parasite infections, feed intake, and digestibility, liveweight (LW) gain, and enteric methane (CH4) emissions. We investigated the legume forage tree, Calliandra calothyrsus, as a high-quality feed rich in crude protein that contains condensed tannins that have the potential to control GIT worms. Twenty-eight Dorper lambs underwent random allocation across four treatments each with seven lambs. Treatments combined either infection or no infection with Haemonchus contortus with supplementation of Rhodes grass hay with dried Calliandra leaflets. The treatments were: UnHay (uninfected, fed on hay-only), InHay (infected, fed on hay-only), InHay+Cal (infected, fed on hay plus Calliandra), and InHay+Cal+PEG (infected, fed on hay, Calliandra, and polyethylene glycol (PEG)). The latter was to evaluate the potential effects of Calliandra's condensed tannins. The results show that lambs in the InHay+Cal treatment exhibited a higher packed cell volume (PCV) and lower faecal egg counts (FEC) compared to the InHay group. Calliandra supplementation increased total feed dry matter intake (DMI) and enhanced LW gain, whereas the unsupplemented infected group (InHay) experienced LW loss. Calliandra supplementation to infected lambs reduced daily CH4 emission by 15% and CH4 yield (g/kg DMI) by 30%, compared to emissions from unsupplemented infected lambs. Calliandra supplementation decreased the digestibility of crude protein and fibre and raised the faecal nitrogen (N) output to N intake (FN/NI) ratio. The effects of PEG supplementation on CT activity remained inconclusive. These findings underscore the considerable advantages of integrating Calliandra into farming systems. Such nature-based solutions control GIT parasite infections, improve nutrient supply and animal productivity cost-effectively, and mitigate enteric methane emissions.